Attitudes of contemporary Saudi plastic Artists towards the National Saudi Arabia’s Vision 2030 to enriching the plastic art in the Kingdom of Saudi Arabia - Almalki, Alhanouf Ahmad; Alzaid, Salma Salem (Journal of Educational and Psychological Sciences, 2022)
The current study aims to identify the contemporary plastic arts in the Kingdom of Saudi Arabia and reflecting the importance of 2030 National Vision in enriching the contemporary plastic arts in the Kingdom and to know the attitudes of Saudi Plastic Artists for 2030 National Vision. The study was applied for an appropriate sample of Saudi Plastic Artists in different areas of the Kingdom, they were selected by random sampling technique through social media networks programs and the Art institutions which affiliated by some artists, where the researcher has sent (350) e-questionnaire to be filled by the Artists, she has received (305) completed and valid questionnaire for statistical analysis with a response rate of (87.1%). The study was focused on two subjects, the contemporary plastic art in the Kingdom and the role of National Vision 2030 for enriching the contemporary plastic arena. - The participants of study "the contemporary Saudi Plastic Artists" totally agreed to the importance of the National Vision 2030 in enriching the plastic field in the Kingdom of Saudi Arabia and the overall average of their agreement is (2.74 out of three) and with standard deviation of (0.34). - The attitudes of contemporary Saudi Plastic Artists is quite positive for the National Vision 2030 regarding enrichment of the plastic art area in the kingdom of Saudi Arabia and the overall average of their response (2.76 out of three) and with standard deviation of (0.33). - The attitudes of contemporary Saudi Plastic Artists matching the interest of National Vision 2030 beside investment in plastic arts both inside and outside the Kingdom as they consider it as successful idea.